Diagnosis of hhv8 infection (Hematology Meeting Reports, 2009)
Before 1994, the idea that an infectious agent played a role in Kaposi’s sarcoma, was nothing more than a strong suspicion. In that year, human herpesvirus 8 (HHV8) was identified in KS tissue. HHV8, also known as Kaposi’s sarcoma-associated Herpesvirus (KSHV), belongs to the Gammaherpesvirinae subfamily of genus Rhadinovirus and is the first member of the genus shown to infect humans. The discovery of the role of HHV8 in KS is a good example of how molecular and epidemiological approaches can work together to identify previously unknown infectious agents. Subsequent research has shown that HHV8 is associated with all variants of KS (AIDS KS, classic KS, endemic KS and iatrogenic KS) as well as with two rare lymphoproliferative diseases: primary effusion lymphoma (PEL) and the multicentric Castleman’s disease (MCD).